Electroconvulsive Therapy Regulates the Interhemispheric Functional Connectivity of the Dorsomedial Prefrontal Cortex in Depressive Patients: Evidence from 2 Independent Samples. - Loufeng Zhang; Yuanyuan Guo; Tongjian Bai; Meidan Zu; Qiang Wei; Yue Wu; Gongjun Ji; Huaming Lv; Wen Xie; Kai Wang; Yanghua Tian; Jingyong Su (Actas Espanolas de Psiquiatria, 2024)
Background: The dorsomedial prefrontal cortex (dmPFC) is considered a crucial node in emotional and cognitive processes. Voxel-mirrored homotopic connectivity (VMHC) is a validated methodology for investigating interhemispheric coordination. This study aims to elucidate the effects of electroconvulsive therapy (ECT) on the interhemispheric connectivity of the dmPFC in patients with depression, using VMHC as a measure of bilateral neural coordination. Methods: Thirty-three patients with depression, screened at the University of Science and Technology of China (USTC), and thirty-five patients with depression, screened at Anhui Medical University (AHMU), were selected as the subjects of this study. VMHC was employed to investigate the effects of ECT on bilateral hemispheric functional connectivity. The Hamilton Depression Rating Scale (HAMD) was used to assess depressive symptoms, and the relationships between changes in HAMD scores and VMHC values were examined. Results: Following ECT, the depressive symptoms of all participants decreased (p < 0.001). The VMHC values in the dmPFC were significantly increased in both groups after ECT (p < 0.01). No significant correlation was found between the increasing VMHC values in the dmPFC and the changes in HAMD scores in depressed patients (p > 0.05). Conclusion: These results show that ECT regulates interhemispheric functional connectivity in depressed patients, and significantly increases the VMHC values in the dmPFC. Our findings may provide a useful method for optimizing the treatment of depression.